Africa's Pulse, October 2010 : An Analysis of Issues Shaping Africa's Economic Future - World Bank (Washington, DC, 2014)
This Africa's pulse newsletter includes the following heading: recent economic trends and prospects; country policy and institutional assessment: results and trends for Sub-Saharan Africa; and Sub-Saharan Africa: advancing toward the millennium development goals (MDGs).